Initial Study of Public Address Usage in Mosque Audio Systems - Safiq Rosad; Anton Yudhana; Tole Sutikno (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2025)
Abstract - The use of mosque audio systems as daily necessities, ensuring the message can be heard clearly, having a pleasant experience, and the congregation is more comfortable lingering while walking. People in Indonesia are accustomed to calling the type of audio system intended for mosques by calling one brand, even though this is the name of a loudspeaker manufacturing company that focuses on audio systems for public spaces, and in fact there are many other similar manufacturers, and this audio system is called Public Address (PA). This study aims to prove the type of PA, maintenance, problems, and handling of audio system problems that are often faced in the mosque environment. The research method used is descriptive qualitative which describes a phenomenon that occurs in the mosque environment, with data collection through questionnaires, and aims to verify existing knowledge and assess its validity. The results obtained from the distribution of a population of 200 mosques, resulted in 93,1% of mosques using the same PA manufacturer brand, but the satisfaction level was only 47,2%. The influencing factors are that 60% of the takmir/congregation are only users, and the average age of the takmir/congregation is 50 years and above or an age that is no longer productive and more protective of new technology. This study also discusses proposals for the development of PA in the future that can especially in active amplifiers (Self-applified) using decentralized rules which are distributed on ready nodes (speakers) with the aim of adaptability to room acoustics.